Ultrasensitive and highly selective electrochemical sensing of sodium picrate by Dihydroxylatopillar[6]arene-Modified gold nanoparticles and cationic Pillar[6]arene functionalized covalent organic framework. (1st March 2020) - Tan, Xiaoping; Fan, Yumin; Wang, Sheng; Wu, Yan; Shi, Wenbing; Huang, Ting; Zhao, Genfu
Abstract: Ultrasensitive, high selective and rapid monitoring of explosives has increasingly become a crucial and urgent challenge in order to protect environment and prevent terrorist threats, which should be addressed timely. In this study, a highly selective and sensitive electrochemical sensing platform based on two dimensional (2D) heterogeneous functionalized material for determination dangerous and explosive sodium picrate (SP) and analogue picric acid (PA) is successfully established. To begin with, the dihydroxylatopillar [6]arene (2HP6) modified Au nanoparticles (2HP6@Au) can be easily obtained by 2HP6 reduced and stabilized Au nanoparticles at room temperature. Then, assembly of 2HP6@Au on the surface of cationic pillar [6]arene (CP6) functionalized covalent organic framework (COF) can obtain 2D heterogeneous composite (2HP6@Au@CP6@COF) for rapid and sensitive detection of SP. The electrode, best operated at a working potential of −0.4 to −1.1 V (vs. Hg/Hg2 Cl2 ), works in the concentration range of 0.005–120 μM SP and has a 0.0017 μM detection limit. The Au nanoparticles play an electrocatalytic role in sensing SP, the 2HP6 and CP6 serve as a prominent material for gathering and recognition SP onto the surface of electrode, respectively. The SP can thread into the cavity of pillar [6]arene and form a 1:1 [2]pseudorotaxanetype complex. The SP can be highly captured by CP6 via the excellent supramolecular host-guest interactions (including π interaction, hydrophobic interactions and electrostatic interactions). Consequently, this work might present a green strategy for preparation 2D heterogeneous functionalized hybrid material in catalysis, sensing and other fields. Graphical abstract: Schematic illustration of the 2HP6@Au@CP6@COF hybrid nanomaterial application in sensing towards sodium picrate. Image 1